Effects of alcoholic fermentation on the non-volatile and volatile compounds in grapefruit (Citrus paradisi Mac. cv. Cocktail) juice: A combination of UPLC-MS/MS and gas chromatography ion mobility spectrometry analysis - Cao, Xuedan; Ru, Shuijiang; Fang, Xiugui; Li, Yi; Wang, Tianyu; Lyu, Xiamin (Frontiers in Nutrition, 2022)
Grapefruit has attracted much attention as a functional fruit, of which “Cocktail” is a special variety with low acidity. The present study aimed to investigate the effects of alcoholic fermentation on the non-volatile and volatile compounds of “Cocktail” grapefruit juice. To analyze, a non-targeted metabolomics method based on UPLC-MS/MS and volatiles analysis using GC-IMS were performed. A total of 1015 phytochemicals were identified, including 296 flavonoids and 145 phenolic acids, with noticeably increasing varieties and abundance following the fermentation. Also 57 volatile compounds were detected, and alcoholic fermentation was effective in modulating aromatic profiles of grapefruit juice, with terpenes and ketones decreasing, and alcohols increasing together with esters. Citraconic acid and ethyl butanoate were the most variable non-volatile and volatile substances, respectively. The results provide a wealth of information for the study of “Cocktail” grapefruit and will serve as a valuable reference for the large-scale production of grapefruit fermented juice in the future.